2023
DOI: 10.1002/jcsm.13336
|View full text |Cite
|
Sign up to set email alerts
|

Stimulator of interferon genes promotes diabetic sarcopenia by targeting peroxisome proliferator activated receptors γ degradation and inhibiting fatty acid oxidation

Sen‐bo Yan,
Huan Liang,
Peng Zhan
et al.

Abstract: BackgroundDeclined skeletal muscle mass and function are inevitable consequences of long‐term diabetes and bring about many adverse events. Muscle fibre atrophy and interstitial fibrosis are major pathological manifestations of diabetic sarcopenia. Stimulator of interferon genes (STING) participates in various metabolic diseases. We aimed to explore whether and how STING regulates the above pathological manifestations of diabetic sarcopenia.MethodsWild‐type and STINGgt/gt C57BL/6J mice and C2C12 myotubes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The acceleration of population aging had led to an increased prevalence of DS, characterized by elevated rates of falls, functional disability, and fractures. More research spanning from basic science to clinical studies, has revealed the complexity of DS, however, no specific treatments have been established. Therefore, it is crucial to identify new targets for sarcopenia, muscle mass, and function loss caused by sustained hyperglycemia. In our present study, we comprehensively investigated the interactions of gut–muscle axis by evaluating multiomics, including gut microbiome, gastrocnemius metabolome, and proteome.…”
Section: Discussionmentioning
confidence: 99%
“…The acceleration of population aging had led to an increased prevalence of DS, characterized by elevated rates of falls, functional disability, and fractures. More research spanning from basic science to clinical studies, has revealed the complexity of DS, however, no specific treatments have been established. Therefore, it is crucial to identify new targets for sarcopenia, muscle mass, and function loss caused by sustained hyperglycemia. In our present study, we comprehensively investigated the interactions of gut–muscle axis by evaluating multiomics, including gut microbiome, gastrocnemius metabolome, and proteome.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is a geriatric syndrome characterized by aging-related loss of skeletal muscle mass, strength, and function, leading to adverse outcomes such as frailty, disability, fractures, and even death in the elderly population . While sarcopenia occurs primarily in older people, it can also occur secondary to chronic diseases, particularly diabetes mellitus, which is termed diabetes-related sarcopenia. , Type 2 diabetes mellitus (T2DM) is the most common metabolic disease in the world and manifests as an abnormal hyperglycemic state due to insulin resistance (IR) and insulin insufficiency . T2DM is considered as a risk factor for numerous micro- and macrovascular complications, imposing a serious burden on public health .…”
Section: Introductionmentioning
confidence: 99%